Dividend Policy and Value of Quoted Firms in Nigeria: A Test of Miller and Modigliani Irrelevant Hypothesis - Lucky, Lucky Anyike; Onyinyechi, Uzokwe Grace (Australian Finance & Banking Review, 2019)
This study tested Miller and Modigliani dividend policy irrelevant hypothesis in Nigeria. The objective was to examine the validity of the irrelevant hypothesis. Tobins Q measure of market value was modeled as the function of dividend payout ratio, retention ratio, dividend per share and dividend yield. 20 firms  were selected on the basis of availability of information necessary for conducting the study and the readiness of annual financial reports for the period of 10 years from 2008-2017.  Cross sectional data was sourced from financial statement and annual reports of the firms. Based on the analysis of fixed and random effect results, random effect was used. The study revealed that 75 percent variation on the market value can be predicted by variation on independent variables in the regression model. The beta coefficient of the variables found that all the independent variables have positive and significant relationship with market value of the selected quoted firms. The study concludes that dividend policy is relevant as oppose to the irrelevant hypothesis of Miller and Modigliani. Its therefore recommend that managers should manage their dividend policies effectively since it is relevant and has significant effect on market value and optimal dividend policy which implies policy of trade-off between dividend payout and retain earnings should be well managed and investors should have adequate knowledge of dividend policy of quoted firms that will correspond with their investment objectives of avoid conflict in dividend policy.